Female Labor Force Status and Couple's Marital Satisfaction: A Chinese Analysis - Yu, Xiao; Liu, Shu (Frontiers in Psychology, 2021)
While China has decreasing female labor participation and increasing marital instability, compared to the rest of the world, its female labor participation rate is higher on average. The effect of female labor force status on couples’ marital satisfaction, as one of the main factors for evaluating marital quality, has been separately discussed, including extensive margins considering whether women are in the labor market and intensive margins on women working hours per week. This study analyzed data from the 2014 China Family Panel Studies using a binary logit model and a stability test. Results showed that the work hours, rather than the occupational status, of women affect marital satisfaction. In addition, regardless of the gender role attitudes held by the couple, marital satisfaction increases when women are in the labor market. This study has retroactively reviewed the effects of women working outside the home on marital quality. The dual roles of Chinese women, as both employee and homemaker, have been socially accepted. However, the requirements of maintaining multiple roles often contradict and present conflicts among the roles, time, and pressure, in the long run, giving rise to marital dissatisfaction.